2005
DOI: 10.1002/chin.200550032
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ring Opening of meso‐Epoxides Catalyzed by the Chiral Phosphine Oxide BINAPO.

Abstract: Enantioselective syntheses O 0031Asymmetric Ring Opening of meso-Epoxides Catalyzed by the Chiral Phosphine Oxide BINAPO. -Bis(phosphine oxide) (S)-BINAPO is an effective catalyst for the synthesis of chlorohydrins from meso-epoxides and tetrachlorosilane. Since the presence of iPr2NEt in the reaction of stilbene oxide dramatically enhances the enantioselectivity, these conditions are also applied to the other epoxides (I) and (III). -(TOKUOKA, E.; KOTANI, S.; MATSUNAGA, H.; ISHIZUKA, T.; HASHIMOTO, S.; NAKAJI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The earliest report of the use of a P-chiral phosphine oxide detailed the application as a ligand for asymmetric transfer hydrogenation of ketones, [6] and subsequent studies have shown applicability in a number of synthetic applications, including Diels-Alder reactions, [7] enantioselective allylation of -hydrazono esters, [8] desymmetrisation of diaryl mesoepoxides, [9] reductive aldol condensations, [10] and reductive cyclisation of N-acylated-amino enones. [11] The latter two transformations make use of trichlorosilane as a reductant, a reagent known for susceptibility for activation by Lewis base catalysts, a majority of which are amide based.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest report of the use of a P-chiral phosphine oxide detailed the application as a ligand for asymmetric transfer hydrogenation of ketones, [6] and subsequent studies have shown applicability in a number of synthetic applications, including Diels-Alder reactions, [7] enantioselective allylation of -hydrazono esters, [8] desymmetrisation of diaryl mesoepoxides, [9] reductive aldol condensations, [10] and reductive cyclisation of N-acylated-amino enones. [11] The latter two transformations make use of trichlorosilane as a reductant, a reagent known for susceptibility for activation by Lewis base catalysts, a majority of which are amide based.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, aside from the well-known triphenylphosphine oxide, plenty of novel phosphine oxides have been designed and synthesized as useful molecules for both industry and academia. For example, the chiral phosphine oxide compound A (BINAPO) [ 12 ] and the bisoxazoline phosphorus ligand B [ 13 ] have been employed as a catalyst or ligand to catalyze versatile asymmetric reactions; the phosphorus chromones C is a progesterone receptor antagonist [ 14 ]; compound D is known as a preeminent flame retardant [ 15 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epoxides play an important role in organic synthesis as a variety of nucleophiles can be employed in the ring opening reactions. Denmark et al 68 Nakajima's group reported that also chiral phosphine oxide (S)-BINAPO 71 can catalyze the enantioselective ring opening of meso-epoxides in the presence of tetrachlorosilane, affording the corresponding chlorohydrins in high enantioselectivities (up to 90% ee) (Figure 1.30b).…”
Section: Ring Opening Reaction Of Epoxidesmentioning
confidence: 99%